Deploying Linux on the desktop - Haletky, Edward (Burlington, MA : Elsevier Digital Press, 2005)
This book will meet the needs of those LINUX users who wish to set up a desktop LINUX workstations, and integrate them into their corporate environment. It will provide practical answers to such questions as: a) What tools do I use to fully integrate with the Microsoft Office tool suite? b) How do I set up my email and interact with a Microsoft Exchange Server? c) Where can I obtain, and how do I install, Internet browser plug-ins needed for web access, media playing, and other corporate Internet functionality? Provides a guide to using LINUX on the desktop for the corporate user. It will cover more than basic topics, such as whether to use OpenOffice or use another tool such as Evolution; they will delve into specific configurations necessary to interact efficiently with the Microsoft centric world of the Desktop. This guide will cover those problem areas that arise and discuss how to smooth over the bumps while meeting the goal of using a LINUX desktop. Lastly this book will cover whether or not a complete LINUX solution is available, or if some hybrid desktop will be needed to interact smoothly in the modern corporate computing environment; including a discussion of necessary LINUX growth directions for future expansion and capability. Reviews real world requirements. Covers Pure LINUX, and Hybrid Corporate Desktops. Covers Enabling Tools such as CrossOver Office and the use of Windows Native programs on LINUX. Reveals Interoperability Concerns. Implements a solid Corporate Desktop. Reviews the complete costs of Implementing LINUX as a desktop.
The requirements -- Virtual private network (VPN) connectivity -- Office -- Multimedia, web browsing, and publishing -- File sharing -- Messaging -- Terminal emulators and server clients -- Home office tools -- Virus and spam protection -- Training tools -- An investigative approach -- Conclusion and future directions -- My recipe.
Includes index.
Keywords: Linux; Operating systems (Computers).; Electronic books